(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: The insistent range of coronavirus (COVID-19) crisis and its permeation into least developed countries has escalated the bar of countries fragility and susceptibility. Afghanistan is amongst the most affected countries by the COVID-19 pandemic certainly due to its poor health infrastructure and conflict affected demography. Objective: This study intends to assess the health vulnerability profile and identifying the control mechanism of the north and northeast regions of Afghanistan using the IPCC framework. Method: A pre-evaluated online questionnaire (Google form) and mobile survey of 361 households distributed in 8 provinces across the both zones to collected the primary data. Exposure, sensitivity and adaptive capacity covered the three main components of vulnerability index, weighing method of Iyenger and Sudershan is used to estimate the fabricate vulnerability index. Result: The province’s health vulnerability status was classified to the different groups based on beta distribution. Based on the vulnerability index, 62.5% of provinces were highly vulnerable, 25% moderately and 37.5% were least vulnerable. Conclusion: In north-east region people were highly vulnerable to COVID-19 in terms of sensitivity and exposure, with low copping capacity to cope with COVID-19 pandemic risks compare to the north zone. Recommendation: Enhancing health and hygiene facilities and a handful of lowcost methods such as strengthen informal safety nets and introducing small-scale regional infrastructure projects, could be most cost effective and viable options. Originality: The research work is original and has not been published in other publications. As well, no financial support has been received for the study.